Large Group Exposure Treatment: a Feasibility Study in Highly Spider Fearful Individuals - Wannemueller, André; Appelbaum, David; Küppers, Maike; Matten, Amelie; Teismann, Tobias; Adolph, Dirk; Margraf, Jürgen (Frontiers in Psychology, 2016)
A large group one-session exposure treatment (LG-OST) based on indirect modeled exposure strategies was carried out to investigate its feasibility and effectiveness in a sample of highly spider fearful individuals (N = 78). The stability of LG-OST-effects was assessed at 8-month follow-up (FU). Furthermore, a second sample (N = 30) of highly spider fearful individuals was treated in a standard, single-person one-session treatment (SP-OST) design to compare LG-OST-effects to a standard spider fear treatment. Participants’ fear of spider was assessed by multiple questionnaires and by a behavioral approach test (BAT). The fear assessment took place before and after the respective intervention, and at 8-month follow-up in LG-OST. Regarding subjective spider fear measures, LG-OST mainly showed medium to large effect sizes, ranging from Cohen’s d = .69 to d = 1.21, except for one small effect of d = .25. After LG-OST, participants approached the spider closer at post-treatment measures (d = 1.18). LG-OST-effects remained stable during the 8-month FU-interval. However, SP-OST-effects proved superior in most measures. An LG-OST-protocol provided evidence for feasibility and efficiency. The effects of LG-OST were equal to those of indirect modeled exposure strategies, carried out in single-settings. LG-OST may represent a useful tool in future phobia-treatment, especially if it can match the effects of single-setting OST, e.g., by including more direct exposure elements in future large group attempts.